(8х-3)²•х-(4х-1)³=7 подробно и с проверкой

Anotherdream Anotherdream    1   05.09.2021 16:25    0

Ответы
Sniper2016 Sniper2016  05.09.2021 16:30

(8х-3)²×х -(4х-1)³=7

64х³-48х²+9х-64х³+48х²-12х+1-7=0

-3х-6=0

-3х=6

х=-2

(8(-2)-3)²×(-2)-(4(-2)-1)³=7

361×(-2)+729=7

-722+729=7

7=7

Р S применили формулы:

(a-b)²=a²-2ab+b²

(x-y)³=x³-3x²y+3xy²-y³

³

ПОКАЗАТЬ ОТВЕТЫ
5765314680 5765314680  05.09.2021 16:30

применяем формулы СУ

(a - b)² = a² - 2ab + b²  

(a - b)³ = a³ - 3a²b + 3ab² - b³

 

(8х-3)²•х-(4х-1)³=7  

(64x² - 48x + 9)*x - (64x³ - 48x² + 12x - 1) = 7  

64x³ - 48x² + 9x - 64x³ + 48x² - 12x + 1 = 7  

-3x = 6

x = - 6/3  

x = -2  

проверка  

(8*(-2) - 3)²*(-2) - (4*(-2) - 1)³ = -2*(-16 - 3)² - (-8 - 1)³ = -2*(-19)² - (-9)³ =

= -2*361 + 729 = -722 + 729 = 7

ПОКАЗАТЬ ОТВЕТЫ